Environmental Health Class On Field Day, 1993 #1 - Missouri Southern State University (1993)
Environmental Health Class on Field Day, 1993, 1-3 depict a faculty member touring an industrial facility for educational purposes. This includes one faculty member, three students (or possibly two students and an employee to the facility).